Cost Implications of Varying the Surgical Setting and Anesthesia Type for Dorsal Wrist Ganglion Cyst Excision Surgery. Issue 2 (25th January 2022) - Steadman, Jesse N.; Stephens, Andrew R.; Wei, Guo; Presson, Angela P.; Kazmers, Nikolas H.
Abstract : Background: Minimizing expenses attributed to dorsal wrist ganglion cyst excisions, a common minor surgical procedure, presents potential for health care cost savings. Varying the surgical setting (operating room versus procedure room) and type of anesthesia (local-only, monitored anesthesia care, or monitored with regional or general anesthesia) may affect total operative costs. Methods: Patients who underwent an isolated unilateral dorsal wrist ganglion cyst excision between January of 2014 and October of 2019 at a single academic medical center were identified by CPT code. The total direct costs for each surgical encounter that met inclusion criteria were calculated. The relative total direct costs were compared between surgical setting and anesthesia type groups. Univariate and multivariable gamma regression models were used to identify factors associated with surgical costs. Results: A total of 192 patients were included; 26 cases (14 percent) were performed in the procedure room and 166 cases (86 percent) were performed in the operating room. No significant differences in demographic factors were identified between groups. Univariate analysis demonstrated that use of operating room/monitored anesthesia care, operating room/monitored anesthesia care with regional anesthesia, and operating room/general anesthesia groups, as compared to procedure room/local-only, yielded significantly greater median costs (1.76-, 2.34-, and 2.44-fold greater, respectively). Multivariable analysis demonstrated 1.80-, 2.10-, and 2.31-fold greater costs with use of operating room/monitored anesthesia care, operating room/monitored anesthesia care with regional anesthesia, and operating room/general anesthesia relative to procedure room/local-only, respectively. Conclusion: Performing dorsal wrist ganglion cyst excisions in a procedure room with local-only anesthesia minimizes operative direct costs relative to use of the operating room and other anesthetic types.